Penyelesaian Sengketa Hak Cipta antara Pencipta Lagu dan Penyanyi - De Fila Asmara, Callesta Aydelwais; Arifin, Zaenal; Mubarok Anwar, Fahruddin (JURNAL USM LAW REVIEW, 2023)
The purpose of this research is to examine the resolution of copyright disputes between Ahmad Dhani and Once Mekel from the perspective of the Copyright Law and legal protection for copyright holders. Copyright infringement of songs by performing cover versions of songs at concerts or musical performances is one of the issues related to copyright violations in Indonesia. Copyright infringement occurs when a singer, without the permission of the song's creator, performs a song at a commercial music concert that violates both moral and economic rights. This research uses a normative juridical method. Based on the research results, it is evident that the legal protection of song copyright holders is accommodated in Law No. 28 of 2014 concerning Copyright. Legal protection for song copyright is an effort to ensure the certainty of fulfilling the rights of copyright holders, both in terms of moral rights and economic rights. Protection of song copyright can be done preventively and repressively. As for the resolution of the dispute between Ahmad Dhani and Once Mekel, it was ultimately resolved through non-litigation dispute resolution through mediation.Tujuan penelitian ini untuk mengkaji penyelesaian perselisihan hak cipta antara Ahmad Dhani dan Once Mekel tinjauan dari Undang-Undang tentang Hak Cipta dan perlindungan hukum pemegang hak cipta. Pelanggaran hak cipta karya lagu dengan cara menyanyikan ulang lagu di konser atau pentas musik merupakan salah satu topik permasalahan dalam pelanggaran hak cipta di Indonesia. Pelanggaran hak cipta terjadi ketika penyanyi tanpa seizin dari pencipta lagu menyanyikan lagu pada konser musik komersial yang melanggar hak moral dan hak ekonomi. Penelitian ini menggunakan metode  yuridis normatif. Berdasarkan hasil penelitian menunjukkan perlindungan hukum pemegang hak cipta lagu diakomodir di Undang-Undang No 28 Tahun 2014 tentang Hak Cipta. Perlindungan hukum atas hak cipta lagu merupakan upaya yang menjamin adanya kepastian pemenuhan hak pemegang hak cipta lagu, baik itu berupa hak moral maupun hak ekonomi. Perlindungan hak cipta lagu dapat dilakukan dengan cara preventif dan represif. Mengenai penyelesaian sengketa Ahmad Dhani dan Once Mekel pada akhirnya diselesaikan melalui penyelesaian sengketa non litigasi dengan cara mediasi.